Princess White Deer’s Show Blanket: Brokering Popular Indigenous Performance Across International Borders - Bold, Christine (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (Graduate Centre for the Study of Drama, University of Toronto, 2020)
This article focuses on Esther Deer, also known as Princess White Deer, and her family of Mohawk performers from Caughnawaga and St. Regis (now Kahnawà:ke and Ahkwesáhsne) in the late nineteenth and early twentieth centuries, a period often considered the nadir of genocidal policies and practices against the Peoples of Turtle Island. Working, as a settler scholar, with the Princess White Deer Collection in the Kanien’kehá:ka Onkwawén:na Raotitióhkwa Language and Cultural Center and with voluminous non-Indigenous press coverage, Bold reconstructs and reads details of the Deers’ acts on the international circuit. In their choreography of spectacle and control of theatrical space, their management of their own labour and their address to their audiences, they seem not only to seize agency in the entertainment marketplace but also to sustain intergenerational family, kinship, and community relations. The most visible marker of their border-crossing mobility and cultural brokerage lies in the layers of their performance attire—the topmost of which is the show blanket, especially as wielded by Princess White Deer.